1997
DOI: 10.1074/jbc.272.13.8222
|View full text |Cite
|
Sign up to set email alerts
|

The Chemical Modification of KCa Channels by Carbon Monoxide in Vascular Smooth Muscle Cells

Abstract: The chemical modification of big conductance calcium-activated potassium (K Ca ) channels in rat tail artery smooth muscle cells by carbon monoxide (CO) was investigated using the cell-free single channel recording technique. Exposure of the internal surface of cell membranes to diethyl pyrocarbonate (DEPC) neither affected the characteristics of K Ca channels nor modified the stimulatory effect of CO on K Ca channels. However, when DEPC was applied to the external surface of cell membranes, the open probabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
170
1
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 226 publications
(177 citation statements)
references
References 26 publications
4
170
1
2
Order By: Relevance
“…This finding is consistent with an earlier suggestion that histidine may be important (26), although the original study implicated extracellularly accessible histidine residues. The reason for the histidine requirement is not entirely clear.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This finding is consistent with an earlier suggestion that histidine may be important (26), although the original study implicated extracellularly accessible histidine residues. The reason for the histidine requirement is not entirely clear.…”
Section: Discussionsupporting
confidence: 83%
“…A previous study has implicated the importance of extracellularly accessible histidine residues in the overall stimulatory effect of CO on native vascular BK channels (26). We found that pretreatment of the Slo1 channel with the histidine modifier diethyl pyrocarbonate (DEPC) applied intracellularly eliminated the stimulatory action of CO ( Fig.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…With a holding potential of À60 mM and in the absence of Ca 2 þ from the bath solution, neither voltage-dependent K þ channel nor calcium-activated K þ channels would have been activated. 26,27 H 2 S at 100 mM significantly increased K ATP channel currents that were subsequently inhibited by gliclazide (1 mM), a classical K ATP channel blocker, 28,29 in b-cells from both ZL (Figure 7a) and ZDF rats (Figure 7b). The amplitude of K ATP channel cur- rents at resting condition appeared to be lower in ZDF b-cells than ZL b-cells (Figure 7c).…”
Section: Insulin Tolerance and Pancreatic Insulin Releasementioning
confidence: 99%
“…There are many proposed cellular targets of CO including soluble guanylate cyclase (sGC) [24] and mitogen-activated protein kinases (for review, see [25]). Recent experiments have also shown CO to play important roles in cardiovascular function [26] and O 2 sensing [27,28] via an activation of large-conductance, calcium-activated potassium channel (BK Ca ). Other ion channels have also been shown to be modulated by CO such as L-type calcium channels (Ca v 1.2) [29], TREK-1 [30] and ENaC channels [31].…”
Section: Introductionmentioning
confidence: 99%